2021
DOI: 10.4018/ijitlhe.20210101.oa1
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Spirituality in the Classroom

Abstract: This study tested the extent to which professors could be trained to help enhance students’ experiences of spirituality in their classes. Three areas of focus that may be important to incorporating spirituality into the classroom were identified in the integration of faith and learning literature: 1) Professor Self-Disclosure, 2) Intellectual Connections, and 3) Interpersonal Connections. In a quasi-experimental design, two professors were trained to incorporate these focus areas into four experimental conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The same barriers observed in our study were also reported by physicians [16,24], highlighting that these barriers should be considered and addressed by educators. Providing S/H training for medical teachers is one of the most important ways to reduce stigmatization and promote the incorporation of S/H content into theoretical and practical classes since training reduces the lack of knowledge and time and encourages faculty to discuss the curriculum [20,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The same barriers observed in our study were also reported by physicians [16,24], highlighting that these barriers should be considered and addressed by educators. Providing S/H training for medical teachers is one of the most important ways to reduce stigmatization and promote the incorporation of S/H content into theoretical and practical classes since training reduces the lack of knowledge and time and encourages faculty to discuss the curriculum [20,25,26].…”
Section: Discussionmentioning
confidence: 99%